Impacts of organizational financialization on supply chain management: an analysis of the Industrial Pole of Manaus - Calvinho, Alexandre Berto (Universidade Federal de São Carlos, 2025)
This research investigates how financialization impacts supply chain management, focusing on the case study of LED lamp production in the Industrial Pole of Manaus (PIM), analyzing the effects of tax incentives from the Manaus Free Trade Zone (ZFM) on production structure and logistical efficiency. The methodology combines a systematic literature review and an empirical case study, with the aim of understanding the fiscal advantages and the logistical challenges resulting from production fragmentation. The study reveals that although production in Manaus involves logistical complexities and additional costs related to transportation and inventory management, the fiscal benefits make it a financially advantageous location. The research highlights that the feasibility of production fragmentation or full relocation should be analyzed on a case-by-case basis, considering the specific cost structures of each industry, as dependence on imported materials and the nature of production can directly influence strategic decisions. The dissertation discusses the trade-offs between fiscal benefits and operational efficiency, emphasizing that financial logic guides strategic decisions, often at the expense of logistical efficiency, as the pursuit of cost minimization and maximization of fiscal benefits prevails over the efficient integration of the supply chain. The research offers practical perspectives for managers, highlighting the need for individualized evaluations and suggests areas for future research, such as the comparison between fragmented and centralized production models and the analysis of different industrial sectors under similar fiscal regimes.
Impactos da financeirização organizacional na gestão da cadeia de suprimentos: uma análise do Polo Industrial de Manaus
Keywords: Financialization; Supply Chain Management; Industrial Pole of Manaus; Tax Incentives; Production Fragmentation; Financeirização; Gestão de Cadeia de Suprimentos; Polo Industrial de Manaus; Incentivos Fiscais; Fragmentação da Produção; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ANALISE DE CUSTOS; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::LOCALIZACAO INDUSTRIAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL::ORGANIZACAO INDUSTRIAL E ESTUDOS INDUSTRIAIS